2008
DOI: 10.1577/a07-062.1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Oxytetracycline Hydrochloride Bath Immersion to Control External Columnaris Disease on Walleye and Channel Catfish Fingerlings

Abstract: The efficacy of oxytetracycline hydrochloride (OTC-HCl) in controlling external columnaris disease caused by Flavobacterium columnare on fingerling walleyes Sander vitreus and channel catfish Ictalurus punctatus was evaluated in two on-site hatchery trials. Microscopic examination of skin scrapings before treatment confirmed the presence of bacteria with characteristics indicative of F. columnare. In separate trials, walleyes (4.4 g) and channel catfish (1.5 g) were exposed to 60-min static bath treatments of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…This result shows that there is a possibility of acute poisoning of these species with the effective concentration of 20.0 mg L -1 OTC recommended by Kubtiza (1997) and Rach et al (2008). At OTC concentrations of 7.5 and 8.0 mg L -1 fishes behavior changed, the lack of ability to pitch, erratic swimming, increased Arq.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…This result shows that there is a possibility of acute poisoning of these species with the effective concentration of 20.0 mg L -1 OTC recommended by Kubtiza (1997) and Rach et al (2008). At OTC concentrations of 7.5 and 8.0 mg L -1 fishes behavior changed, the lack of ability to pitch, erratic swimming, increased Arq.…”
Section: Resultsmentioning
confidence: 67%
“…Kubtiza (1997) and Rach et al (2008) found that a dilution of 20.0mg L -1 OTC in the water satisfactorily controls fish infections. Thus, because of this effectiveness in control of infections, OTC can be prospected for aquaculture use, provided it shows risk to aquatic organisms.…”
Section: Terramycinmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have found a lowered resistance to bacterial infections in fish that were pre-infected with parasites (Kotob et al 2016). Fish's increased susceptibility to bacterial infection has been shown in co-infection by monogenean gill parasites (Busch et al 2003;Zhang et al 2015), tissuepenetrating trematode metacercaria (Pylkkö et al 2006), fish lice (Bandilla et al 2006;Lhorente et al 2014) and different ciliated ectoparasites (Evans et al 2007;Xu et al 2009Xu et al , 2012Shoemaker et al 2012). A chronic myxosporean parasite infection decreased the resistance of rainbow trout to bacterial disease even 12 months after exposure to the parasite (Densmore et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Flavobacterium columnare strains differ in their virulence (Suomalainen et al 2006 ; Pulkkinen et al 2018 ) and are capable of causing up to 100% mortality in juvenile salmonids (Suomalainen et al 2005 ). Since there is no effective vaccination available for young salmonids (Sundell et al 2014 ), the only treatment against F. columnare is antibiotics (Rach et al 2008 ).…”
Section: Introductionmentioning
confidence: 99%